A high-performance ethanol gas sensor based on Ce-doped SnO2 nanomaterials prepared by the Pechini method. (January 2022) - Wang, Yongchang; Li, Hairong; Huang, Dandan; Wang, Xudong; Cai, Lina; Chen, Yawen; Wang, Wenjie; Song, Yuzhe; Han, Genliang; Zhen, Bo
Abstract: Ce doped SnO2 composite nanomaterials with different concentrations were prepared by a modified green Pechini method. The crystalline phases, elemental composition, and surface topography of the composite material were characterized by various characterization methods. The test results reveal that the sensor with appropriate Ce doping SnO2 has excellent gas sensing properties for ethanol. The device doped with 2% Ce showed a response as high as 69.4 in 50 ppm ethanol, which is 2.4 times that of the device based on Pure-SnO2 . Moreover, the sensor has a lower optimum operating temperature, better ethanol selectivity, linearity, and stability. The enhancement factors of the sensing characteristics are further discussed. Ce-doped SnO2 nanomaterials prepared by the Pechini method have great application potential in gas sensors.